The Use of the Internet for Learning in Vocational High School - Sanusi, Anwar; Rohendi, Dedi (INVOTEC, 2020)
The internet continues to interact with almost every aspect of life, teachers will have more choices to utilize the Internet into the learning process. This study aims to determine the use of the internet by teachers in vocational high schools based on their age. The results of the study were obtained from interviews with teachers. Data from interviews were processed using qualitative methods. The results of the study describe that teachers use the internet to support their learning process. The findings obtained in this study are that older teachers have conducted software development training, while younger teachers have not yet attended training, attracting younger teachers to be more skilled in internet use than older teachers.